Iron-cobalt oxide shell / two-dimensional nitride / glycan composite antibacterial preservative film as well as preparation method and application thereof

Through the preparation method of iron-cobalt oxidant/two-dimensional nitride/chitosan composite antibacterial plastic wrap, the problem of poor agglomeration and dispersion of nanoparticles in the composite film of nanoenzyme and chitosan is solved, and the mechanical properties of the composite film are improved and the significant antibacterial effect is achieved, and the storage period of food is extended.

CN119751938AActive Publication Date: 2025-04-04SICHUAN AGRI UNIV

Patent Information

Application Number
CN202411983887.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

During the composite film formation process of existing nanoenzymes and chitosan, nanoparticles are prone to agglomeration, poor dispersion, and insufficient mechanical performance improvement, resulting in poor performance of composite film after film formation and antibacteriality needs to be improved.

Method used

The preparation method of iron-cobalt oxidant/two-dimensional nitride/chitosan composite antibacterial plastic wrap was used, and two-dimensional nitride was synthesized by in-situ etching method, and iron-cobalt oxidant was synthesized by hydrothermal method. After ultrasonic treatment, mixed with chitosan solution, and solvent casting method was used to prepare CS/CM composite antibacterial film.

Benefits of technology

A composite film with excellent mechanical properties, excellent dispersion properties, good film formation effect and significant antibacterial properties was obtained, with a bacterial rate of 96.2%-99.8%. After 12 days of storage, the indexes of the grapes such as hardness, weight loss rate, and titration acidity have changed little.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751938A_ABST
    Figure CN119751938A_ABST
Patent Text Reader

Abstract

The invention provides an iron-cobalt oxide / two-dimensional nitride / chitosan composite antibacterial preservative film as well as a preparation method and application thereof, and belongs to the technical field of preparation of chitosan preservative film materials. According to the preparation method, CM is prepared from a two-dimensional nitride and an iron-cobalt oxide by adopting an ice bath ultrasonic method, then the CM is combined with CS, and the CS / CM composite film with good performance is prepared by adopting a solvent tape casting method. CS and CM have good compatibility, and the internal structure of the composite membrane is compact. The CS / CM composite film has excellent mechanical properties, ultraviolet blocking performance and thermal stability. In addition, the CS / CM composite membrane has extremely high inhibition rate on staphylococcus aureus, escherichia coli and aspergillus niger. In a fresh-keeping experiment of preserving Kyoho grapes by using the CS / CM composite film, the grapes still have higher quality after being stored for 12 days. Therefore, CS / CM is a good packaging material and can be widely applied to food preservation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of chitosan cling film materials, and specifically relates to an iron-cobalt oxide / two-dimensional nitride / chitosan composite antibacterial cling film and a preparation method and application thereof. Background Art

[0002] With the change of dietary structure, people's demand for vitamins is increasing. Fruits and vegetables are rich in vitamins, but they are easy to rot. Fresh fruits and vegetables are easily contaminated by microorganisms during harvesting, transportation and storage. Therefore, antibacterial preservation has always been the pursuit of people.

[0003] Kyoho grapes are rich in vitamin A, vitamin B6 and vitamin C, and are often used to supplement the vitamins needed by the human body. In addition, Kyoho grapes are also rich in resveratrol, polymeric proanthocyanidins and catechins, which can play an antioxidant and prevent cardiovascular disease effects. But at the same time, the rich nutrients in Kyoho grapes make them a good place for the growth and reproduction of many microorganisms (such as Staphylococcus aureus, Escherichia coli and Aspergillus niger). If they are not stored properly, it will cause serious economic losses and food safety problems.

[0004] At present, the commonly used preservation methods for grapes include controlled atmosphere preservation, heat treatment preservation and natural extract preservation, etc. These methods all have certain shortcomings. For example, the high carbon dioxide and low oxygen used in the controlled atmosphere preservation method may cause abnormal fruit metabolism and tissue damage; the heat treatment preservation method is prone to cause fruit dehydration, discoloration and damage; the substances extracted by the natural extract preservation method usually have a strong odor, which affects the fruit's sensory organs. Therefore, in the field of grape preservation, it is urgent to develop a new, time-saving, fast, low-cost and efficient preservation method.

[0005] Compared with other storage and preservation methods, the cost of film preservation is lower, and the production method is simple, the performance is stable, and it is more suitable for promotion and application. Plastic film is currently the most common, but due to its low degradability and harmful substances produced during the decomposition process, long-term use will cause serious damage to both the human body and the environment. Therefore, the development of greener and more environmentally friendly films is imperative.

[0006] Chitosan (CS), the only alkaline polysaccharide among natural polysaccharides, has good biodegradability, biocompatibility, non-toxicity, antibacterial properties and other physiological functions, and is widely used in food, textiles, agriculture and other fields. Studies have shown that films prepared with CS as raw materials have better mechanical strength, barrier properties and structural stability than other films such as protein films and fat films. Although CS can interfere with the permeability of microbial cell membranes, its antibacterial properties need to be improved.

[0007] At present, CS is often combined with other bioactive substances (polyphenols, flavonoids, aromatic substances, etc.) to improve its antibacterial properties in order to obtain better food preservation effects. For polyphenols such as tea polyphenols, their stability is greatly affected by environmental factors, and the antibacterial properties of the composite film will be unstable after addition. Catechins, as a commonly used flavonoid, have strong irritation and bitter taste, which will also affect its preservation of food. Commonly used aromatic substances such as plant essential oils have a strong odor, which will bring bad sensory evaluation to food when used for food preservation. Therefore, new composite materials need to be further developed.

[0008] Nanozymes are a class of artificially synthesized substances with excellent stability and enzyme-mimicking activity. They are inorganic nanoparticles that have enzyme-like activity in redox reactions. Therefore, the processed nanozymes have both unique properties and catalytic functions. Nanozymes have the advantages of convenient synthesis, high catalytic activity, high stability and low cost. Reports have shown that nanozymes can be used for food preservation. Currently, the nanozymes used in food preservation composite films mainly include metal nanozymes (Ag and Fe, etc.) and metal oxide nanozymes (TiO2, Fe3O4, CuO, etc.), but both have problems such as packaging material mobility and antibacterial properties that need to be improved.

[0009] Chinese patent document CN 106883465 A (publication date: June 23, 2017) discloses a chitosan composite cling film, which is prepared by compounding modified nano-carbon crystals with chitosan, thereby improving the antibacterial property of the chitosan cling film. However, its bactericidal performance still needs to be improved, and its antibacterial rate against Escherichia coli and Staphylococcus aureus is only more than 90%. At the same time, it does not have the function of scavenging free radicals by enzymes, and its mechanical properties are not high enough.

[0010] On the other hand, although nanozymes have photocatalytic properties, peroxide mimetic enzyme activity and hydrogen peroxide mimetic enzyme activity, and can sterilize more efficiently, since nanozymes are nanoparticles, they are easily agglomerated, resulting in poor dispersion, thus affecting the performance of the composite membrane.

[0011] Therefore, how to compound nanozymes with chitosan membranes to provide a composite membrane material with good dispersion properties, excellent mechanical properties, and significant antibacterial effect has become a technical problem that needs to be solved urgently. Summary of the invention

[0012] The present invention is to solve the above technical problems, thereby providing an iron-cobalt oxide / two-dimensional nitride / chitosan composite antibacterial cling film and its preparation method and application. The technical purpose of the present invention is to solve the problems that the nanoparticles are easy to agglomerate and have poor dispersibility in the existing nanozyme and chitosan composite film forming process, and the mechanical properties are not improved enough, the performance of the composite film after film formation is not good, and the antibacterial property needs to be improved.

[0013] In order to achieve the above technical objectives, the present invention adopts the following solutions:

[0014] The present invention first provides a method for preparing an iron-cobalt oxide / two-dimensional nitride / chitosan composite antibacterial cling film, comprising the following steps:

[0015] (1) adding lithium fluoride to hydrochloric acid to synthesize a two-dimensional nitride with aluminum titanium carbide by an in-situ etching method;

[0016] (2) synthesizing iron-cobalt oxide by a hydrothermal method using ferric chloride hexahydrate, cobalt chloride hexahydrate, sodium acetate and sodium hydroxide;

[0017] (3) mixing the two-dimensional nitride and the iron-cobalt oxide in a weight ratio of 1:1, dissolving the mixture in water, and ultrasonically treating the mixture in an ice bath to obtain a nanozyme composed of the iron-cobalt oxide and the two-dimensional nitride;

[0018] (4) Dissolving chitosan and glycerol in 1% by volume acetic acid solution to prepare a chitosan solution, wherein the mass percentage of chitosan is 3%; then mixing the nanozyme obtained in step (3) with the chitosan solution to obtain a composite solution, and making the volume ratio of the nanozyme 5%. Subsequently, pouring the composite solution after ultrasonic treatment into a mold, drying to obtain a film, cooling to room temperature and then removing the film, the composite antibacterial cling film is obtained.

[0019] The above-mentioned synthesis method provided by the present invention uses iron cobalt oxide (CoFe2O4, CFO) and two-dimensional nitride (MXene) as precursor materials to synthesize iron cobalt oxide / two-dimensional nitride nanozymes (CM) with multiple enzyme-mimicking activities, and then successfully prepares CS / CM composite antibacterial membranes by solvent casting. The inventors have conducted extensive research on the preparation process of the composite membrane and finally found that only when the concentration of the chitosan solution is prepared to 3wt% and the concentration of the nanozyme solution is controlled to 5vol%, can a composite membrane with excellent mechanical properties, excellent dispersion properties, good film-forming effect and significant antibacterial properties be obtained.

[0020] As shown in the results of the embodiments of the present invention, when the concentration of the nanozyme solution is controlled to be higher than 5 vol%, the mechanical properties of the composite membrane are significantly reduced. At the same time, only when the concentration of the nanozyme solution is controlled to be 5 vol%, the film-forming performance of the composite membrane is optimal.

[0021] In addition, the antibacterial performance of the composite film obtained by the scheme of the present invention is extremely significant. Compared with the CS film, the tensile strength, elongation at break and DPPH removal rate of the composite antibacterial film are increased by 23.06%, 54.38% and 356.31%. The antibacterial rates of the composite antibacterial film against Escherichia coli, Staphylococcus aureus and Aspergillus niger under dark conditions are 96.2%, 96.8% and 92.2%; under light conditions for 6 hours, the antibacterial rates reach 99.7%, 99.8% and 97.1%, respectively. On the 12th day of storage, the hardness, weight loss rate, titratable acidity (TA), soluble solids content, Vc content, POD activity and CAT activity of the grapes in the CS / 5% CM composite antibacterial film group were 0.61 Kg / cm 2 ,13.5%, 0.332%, 13.3%, 4.47mg / 100g, 29Ug -1 min -1 and 19Ug -1 min -1 The sensory and physicochemical properties of the composite antibacterial film changed less than those of the other groups, indicating that the composite antibacterial film can effectively reduce the loss of nutrients in food and achieve the purpose of extending the shelf life of food.

[0022] The present invention applies CM to food preservation, which not only expands the application market of CM, but also fills the gap in food packaging. However, a single nanozyme cannot be directly attached to the surface of food, and its dispersion with CS is extremely difficult. The present invention solves the problem of the difficulty of dispersion of the two and the poor performance after film formation.

[0023] Furthermore, in step (4), the volume ratio of the chitosan solution to the nanozyme solution is 19:1.

[0024] The volume ratio of the chitosan solution to the nanozyme solution in the present invention is also critical to the performance of the composite membrane. As shown in the comparative example of the present invention, when the volume ratio of the two is controlled to be less than 19:1, the membrane cannot be formed; and when the volume ratio of the two is controlled to be greater than 19:1, the mechanical properties of the film after being made will be significantly reduced.

[0025] Furthermore, the weight ratio of lithium fluoride to aluminum titanium carbide in step (1) is 1:1; and the synthesis reaction is carried out at 35° C. for 24 hours.

[0026] Furthermore, in step (2), the weight ratio of ferric chloride hexahydrate, cobaltous chloride hexahydrate, sodium acetate and sodium hydroxide is 18:19:90:25.

[0027] Furthermore, the synthesis reaction in step (2) is carried out at 180° C. for 12 hours.

[0028] Furthermore, the hydrothermal method in step (2) is carried out in an ethylene glycol solution.

[0029] Furthermore, the ultrasonication time in step (3) is 0.5 hours.

[0030] Furthermore, the ultrasonic treatment in step (4) is carried out at 40° C. for 4 h.

[0031] The second object of the present invention is to provide an iron-cobalt oxide / two-dimensional nitride / chitosan composite antibacterial fresh-keeping film prepared by the method described above.

[0032] The third object of the present invention is to provide the use of the iron-cobalt oxide chitosan composite antibacterial fresh-keeping film as described above in the preparation of antibacterial fresh-keeping materials for fruits and vegetables.

[0033] The beneficial effects of the present invention are as follows:

[0034] (1) The present invention provides a method for preparing a CS / CM composite membrane using chitosan and nanozymes. Characterization results show that the CS / CM composite membrane has excellent mechanical properties, UV blocking properties and thermal stability.

[0035] (2) The CS / CM composite film prepared by the present invention has a very high inhibition rate against Staphylococcus aureus, Escherichia coli and Aspergillus niger. In the preservation experiment of Kyoho grapes, the grapes still have a high quality after 12 days of storage. Therefore, CS / CM is a good packaging material and can be widely used in food preservation. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The UV-visible absorption changes of different samples to MB (A) and RhB (B);

[0037] Figure 2 TEM images of CM (AB); surface and cross-sectional SEM images of CS / 5% CM (CD) and CS film (EF);

[0038] Figure 3 AFM images (A); Ra and Rq parameters of different films (B);

[0039] Figure 4 XRD (A) and FTIR (B) images of different films;

[0040] Figure 5 UV-visible absorption spectra (A), water contact angles (B) and DSC curves (C) of different films;

[0041] Figure 6 is the DPPH removal rate of different films;

[0042] Figure 7Effects of different films treated with light and darkness on the growth of Escherichia coli (A), Staphylococcus aureus (B) and Aspergillus niger (C);

[0043] Figure 8 The changes of sensory score (A), firmness (B), weight loss rate (C), TA (D), TSS (E), Vc (F), POD (G) and CAT (H) during the grape preservation process;

[0044] Fig. 9 Images of grapes preserved in CS / 5% CM (A), blank (B), CS (C), and PE (D);

[0045] Fig.10 It is a picture of the dispersion between CM and CS;

[0046] Fig.11 This is the case when the volume ratio of CS to CM is 24:1;

[0047] Fig.12 The antibacterial properties of the composite membrane;

[0048] Fig.13 is the thermal stability of the composite film;

[0049] Fig.14 The ultraviolet light absorption performance of the composite film. DETAILED DESCRIPTION

[0050] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described in detail below in conjunction with the embodiments. It is necessary to point out that the following embodiments are only used to explain and illustrate the present invention and are not used to limit the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above invention content still belong to the protection scope of the present invention.

[0051] Example 1

[0052] 1. Experimental Materials and Methods

[0053] 1. Materials

[0054] Kyoho grapes were collected from Hanyuan Family Farm, LB broth and potato dextrose agar medium were purchased from Qingdao Hope Biotechnology Co., Ltd., tryptic soy agar medium was purchased from Sigma-Aldrich, methyl red, bromocresol green, and 1,1-diphenyl-2-trinitrophenylhydrazine were purchased from Shanghai Yuanye Biotechnology Co., Ltd., and the Escherichia coli (10536), Staphylococcus aureus (29213), and Aspergillus niger used in this experiment were provided by ATCC, and other materials were purchased commercially.

[0055] 2. Preparation of CM nanozymes

[0056] (1) Synthesize two-dimensional nitride (MXene) by in-situ etching method: add 1 g lithium fluoride to 20 mL 9 mol / mL hydrochloric acid and stir in an ice bath for 1 h; then add 1 g aluminum titanium carbide and react at 35 °C for 24 h, and collect the MXene powder.

[0057] (2) Synthesizing iron cobalt oxide (CFO) by hydrothermal method: 0.36 g of ferric chloride hexahydrate, 0.38 g of cobalt chloride hexahydrate, 1.8 g of sodium acetate and 0.5 g of sodium hydroxide were dissolved in 40 mL of ethylene glycol solution, mixed evenly and transferred to an autoclave. After reacting at 180 °C for 12 hours, impurities were washed away with deionized water and CFO powder was collected.

[0058] (3) Nanozyme (CM) was synthesized by ice bath ultrasonic method: 5 mg MXene and 5 mg CFO were dissolved in 10 mL deionized water and ultrasonicated on ice for 0.5 h to obtain nanozyme (CM).

[0059] 3. Photodynamic performance of MXene, CFO and CM

[0060] Methylene blue (MB) and rhodamine B (RhB) were used as ·OH scavengers to detect the generation of ·OH. MB and RhB were mixed with the sample, treated with a xenon lamp and in the dark for 10 min, respectively, and their absorbance was measured using a UV-visible spectrophotometer (wavelength = 664 nm, 554 nm).

[0061] 4. Antibacterial activity of MXene, CFO and CM

[0062] Escherichia coli (ATCC 10536) and Staphylococcus aureus (ATCC 29213) are typical Gram-negative and Gram-positive bacteria. Mix 0.5 mL of bacterial suspension with 0.5 mL of sample and irradiate under a xenon lamp for 10 minutes. The sample placed in the dark is used as the control group. Inoculate the treated mixed solution on an agar medium plate using the spread plate method. Culture in a 37°C incubator for 24 hours and count the number of bacterial colonies.

[0063] 5. Preparation of CS / CM composite membrane

[0064] The composite antibacterial film was prepared by solvent casting method using chitosan (CS) and nanozyme (CM) as raw materials, as follows:

[0065] CS (3 wt%) was dissolved in 70 ml of acetic acid solution (1 vol%), stirred at room temperature for 4 h, and then glycerol (1 wt%) was added and stirred for 4 h to obtain a CS solution. CM solutions of different concentrations (1%, 3%, 5% or 7%, vol%) were added to the above CS solution and ultrasonically treated at 40 ° C for 4 h to remove the foam in the solution. The composite solution was then poured onto a transparent glass plate (70 mL) in sequence and placed in an oven at 55 ° C for 4 h to obtain a film. After the film was cooled to room temperature, it was peeled off from the mold and stored in an environment of 25 ° C and 50% relative humidity.

[0066] The preparation method of single CS membrane was the same as the above method, except that CM solution was not added. The single CS membrane and the prepared CS / CM composite membranes with 1%, 3%, 5% and 7% CM were named as: CS, CS / 1%CM, CS / 3%CM, CS / 5%CM, CS / 7%CM, respectively.

[0067] 6. Morphology and structure analysis

[0068] The morphology of CM was studied by high-resolution transmission electron microscopy (HRTEM) at an accelerating voltage of 200 kV. The surface and fracture cross-section of CS and CS / 5% CM were observed by scanning electron microscopy. The composite film was cut into 3 mm × 3 mm size and fixed on a metal sample stage. The X-ray diffraction pattern (XRD) of the film sample was analyzed using a polycrystalline X-ray diffractometer equipped with Cu-Kα radiation. Cu-Ka radiation ( Spectra were recorded at 40 kV, 40 mA. Fourier transform infrared (FTIR) spectra were recorded on a Nicolet 380 FTIR spectrometer equipped with a horizontal attenuated total reflectance (ATR) crystal. 1 The wave number was scanned 32 times and the spectrum was recorded. The surface structure of the film was characterized by atomic force microscopy and the roughness of the film was measured. The transverse profile of the film was drawn using Gwyddion to observe its thickness distribution. The average surface roughness (Ra) and root mean square surface roughness (Rq) of the film were calculated using NanonScope. The surface morphology of the film was comprehensively evaluated.

[0069] 7. Solubility, swelling rate and water content

[0070] The film was cut into a size of (2 cm x 2 cm) and weighed (M1). The film was dried at 105°C to a constant mass (M2). The water content was determined using the following formula (1):

[0071] Water content = (M1-M2) ÷ M1 × 100% (1)

[0072] The films were cut into a size of (2 cm × 2 cm) and dried at 105 ° C to a constant mass (M1). They were placed in a beaker filled with 50 mL of distilled water, covered with plastic wrap, and stored at 25 ° C for 24 h. Next, they were dried at 105 ° C to a constant weight to obtain the final dry mass (M2). The solubility was calculated using the following formula (2):

[0073] Solubility = (M1-M2)÷M1×100% (2)

[0074] After weighing the film, place the film in a beaker containing 50 mL of distilled water, place it at 25°C for 24 hours, and weigh it (M1). Dry the wet film surface with filter paper, weigh the wet film (M2), and calculate the swelling rate using the following formula (3):

[0075] Swelling rate = (M1-M2) ÷ M1 × 100% (3) 8. Thickness and mechanical properties

[0076] The film thickness was measured with a micrometer with an accuracy of 0.01 mm, and the average value of 10 random points on each film was taken as the film thickness. The film was cut into a size of 6 cm × 2 cm and balanced for 48 hours at 25 ° C and 50 ± 1% RH. The tensile strength (TS) and elongation at break (EB) of the film were measured using a digital analyzer. The results were the average value of 10 random points on each film.

[0077] 9. UV blocking properties

[0078] The film was cut into a size of 6 cm x 2 cm and attached to the inner wall of the test tube. The ultraviolet blocking properties of the film were determined by measuring the light absorption of the film in the wavelength range of 200-800 nm.

[0079] 10. Water vapor transmission rate and water contact angle

[0080] The water vapor transmission rate (WVT) test method of the film sample is as follows: the test temperature is 38°C and the relative humidity is 90%. The WVT is calculated using the following formula (4):

[0081] WVT=(ΔM1-ΔM2)÷A×t (4)

[0082] Where:

[0083] WVT—water vapor transmission rate, in grams per square meter 24 hours [g / (m 2 24h)];

[0084] ΔM1—the difference between two measurements of the same test group, in grams (g);

[0085] ΔM2—the difference between two measurements of the same test assembly of the blank sample, in grams (g);

[0086] A—Effective test area, in square meters (m 2 );

[0087] t—test time, in hours (h).

[0088] The water contact angle on the film surface was measured using an optical contact angle measuring device. 5 μL of distilled water was placed on the film surface to easily measure its hydrophobicity; this was repeated 3 times and the average value was taken.

[0089] 11. Thermal analysis

[0090] Differential scanning calorimetry (DSC) experiments were performed using a SIINT instrument. The film (≈5 mg) was placed in a crucible with an empty crucible as a reference. Inert gas (nitrogen) was added and the temperature was increased from 20°C to 200°C at a rate of 10°C / min to determine the thermal stability of the film.

[0091] 12. DPPH removal rate

[0092] DPPH was dissolved in ethanol to obtain a 1 mg / ml solution. The absorbances of the filmless solution and the filmed solution at a wavelength of 516 nm (A0 and A t ), DPPH is calculated using the following formula (5):

[0093] DPPH=(A0-A t )÷A0×100% (5)

[0094] 13. Antibacterial properties of CM / CS composite antibacterial film

[0095] The antibacterial activity of the film samples against bacteria, namely Gram-negative pathogens (Escherichia coli) and Gram-positive pathogens (Staphylococcus aureus), was evaluated. The pure culture of the bacteria to be tested was streaked on a TSA plate and cultured at 37°C for 18-24 hours. Three to five single colonies were picked up with an inoculation loop and mixed thoroughly in 150 mL of LB broth. The culture was shaken at 30°C for 12 hours and the concentration of the bacterial suspension (~10 9 CFU·mL -1 ). 50 mg of the film was divided into centrifuge tubes containing 5 mL of bacterial solution, and a xenon lamp was used for light and dark treatment. After the bacterial solution was diluted to a certain concentration, 100 μL of the bacterial solution was spread on a TSA plate, and the culture dish was placed in a ziplock bag and cultured in a constant temperature incubator for 18-24 hours. The growth status of the culture dish was observed and recorded. The following formula (6) was used to calculate the inhibition rate of bacterial growth by light and dark treatment:

[0096] Growth inhibition rate = (N0-N) ÷ N0 × 100% (6)

[0097] Where:

[0098] N0—total number of colonies in dark treatment;

[0099] N t —Total number of colonies treated with light.

[0100] The antibacterial activity of the film samples against mold, namely Aspergillus niger, was evaluated according to the following method: Aspergillus niger was inoculated on a potato agar (PDA) slant medium and cultured at 30°C for 5 days. The spores on the medium were washed off with sterile water and transferred to a sterile triangular flask. The spores were shaken to break up the spores. After filtering with sterile gauze to remove the hyphae, the concentration of the bacterial solution was adjusted to 10 using a hemocytometer and sterile water. 6 / mL. 50mg of the film was divided into centrifuge tubes containing 5mL of bacterial solution, and a xenon lamp was used for light and dark treatment. After the bacterial solution was diluted to a certain concentration, 100uL of the bacterial solution was spread on the PDA plate, and the culture dish was placed in a ziplock bag and cultured in a constant temperature incubator for 5 days. The growth status of the culture dish was observed and recorded. Formula (6) was used to calculate the inhibition rate of Aspergillus niger growth under light and dark treatment.

[0101] 14. Kyoho grape preservation experiment

[0102] The experiment selected Kyoho grapes of similar maturity and randomly divided them into 4 groups. They were packaged with PE film, CS film alone, CS / 5% CM and no film. They were stored at room temperature and tested every two days.

[0103] (1) Hardness

[0104] The hardness of grapes was measured using a fruit hardness tester.

[0105] (2) Weight loss rate

[0106] At the beginning of the experiment, the grape samples were weighed and marked as (M1). At different times, the grape samples were removed from the packaging and weighed again, marked as (M2). The weight loss rate was calculated using the following formula (7):

[0107] Weight loss rate = (M1-M2) ÷ M1 × 100% (7)

[0108] (3) Titratable acid (TA)

[0109] TA was determined by titration: 5 g of grape pulp was ground into a homogenate and diluted to 50 mL with distilled water. After mixing well, 20 mL of the mixed solution was titrated with 0.01 mol / L NaOH, and 1% phenolphthalein was used as an indicator.

[0110] The titratable acid was calculated using the following formula (8):

[0111] Titratable acid = V 氢氧化钠×0.1×0.064×V0÷m×V1 (8)

[0112] Where:

[0113] V 氢氧化钠 —The volume of NaOH consumed in the titration, in mL;

[0114] V1—molar concentration of NaOH, in mol / L;

[0115] 0064—Citrate conversion factor;

[0116] V0—fixed volume, in mL;

[0117] m—Green field volume, in mL.

[0118] (4) Soluble solids

[0119] The soluble solids content of the grape sample was determined using a handheld sugar meter. 20 g of grape pulp was fully ground with 20 g of oxalic acid solution (20 g / L) under light-proof conditions. After adding a certain amount of white clay, the volume was fixed to 100 mL with oxalic acid solution. After filtering, 10 mL of the filtrate was titrated with 2,6-dichloroindoleoxy alcohol solution. The soluble solids were calculated using the following formula (9):

[0120] X=[(V-V0)×T×A]÷m×100% (9)

[0121] Where:

[0122] V—volume of solution consumed in titration, in mL;

[0123] V0—the volume of the blank test, in mL;

[0124] T—titer, in mg / mL;

[0125] A—dilution factor;

[0126] m—sample weight, in g.

[0127] (5) Vitamin C content

[0128] The Vc content in the sample was determined according to the 2,6-dichloroindophenol titration method in the GB / T 5009.86-2016 standard.

[0129] (6) POD activity

[0130] 3 g of grape pulp was mixed with 5 mL of phosphate buffer for 30 min, and the supernatant was collected by refrigerated centrifugation. 0.5 mL of the supernatant was mixed with 2.5 mL of 0.3% catechol solution and 0.2 mL of 2% H2O2. The absorbance of the mixed solution was measured within 3 min (wavelength = 470 nm). The blank control was pure distilled water. The POD activity was calculated using the following formula (10):

[0131] POD=ΔOD 470 ×V÷(0.01×V s ×m) (10)

[0132] Where:

[0133] POD—peroxidase activity, unit is U·g- 1 ·min- 1 ;

[0134] V—total volume of sample extract, in mL;

[0135] V S —The total volume of sample extract taken during the determination, in mL;

[0136] m—sample weight, in g.

[0137] (7) CAT activity

[0138] 3 g of grape pulp was mixed with 5 mL of phosphate buffer for 30 min, and the supernatant was collected by refrigerated centrifugation. 0.1 mL of the supernatant was mixed with 2.9 mL of H2O2 (20 mmol / L) and the absorbance of the mixed solution was measured (wavelength = 240 nm). The CAT activity was calculated using the following formula (11):

[0139] CAT=ΔOD 240 ×V s1 ÷(0.01×V s2 ×m2) (11)

[0140] Where:

[0141] CAT—catalase activity, unit is U·g- 1 ·min- 1 ;

[0142] V S1 —Total volume of sample extract, in mL;

[0143] V S2 —The total volume of sample extract taken during the determination, in mL;

[0144] m2—sample weight, in g.

[0145] 2. Experimental Results

[0146] 1. CM photodynamic performance

[0147] In order to determine the photodynamic properties of different materials, MB and RhB were used as OH scavengers. Figure 1 As shown in A and B, the absorption peaks of CFO and Mxene at 664nm and 554nm did not change significantly before and after illumination, indicating that CFO and Mxene did not produce sufficient ·OH to degrade MB and RhB after illumination. However, the absorption peaks of CM at 664nm and 554nm decreased significantly before and after illumination, indicating that CM has a significant ability to generate ·OH and excellent photodynamic properties.

[0148] 2. Morphology and structure

[0149] TEM images of CM are shown in Figure 2. Figure 2 As shown in A and B. The synthesized CM has good dispersion. Combining high-magnification and low-magnification TEM images, it can be seen that the spherical CFO nanoparticles are tightly adhered to the monolayer MXene. The high-magnification TEM image shows clear lattice fringes, the lattice spacing of CFO is 0.256nm, the lattice spacing of MXene is 0.473nm, and the spherical CFO nanoparticles are deposited on the MXene surface, indicating that the CM was successfully synthesized.

[0150] The cross-sectional and surface scanning electron microscopy images of CS membrane and CS / 5% CM composite membrane are shown in Figure 2. Figure 2 As shown in Figure CF, the two films show similar morphology and no cracks appear on the surface. The surface of the CS film is smooth and dense, and the cross section shows a rich porous structure. With the addition of CM, the roughness of the film surface increases. The reduction of the original structural voids in the CS matrix can increase the resistance of water molecules to diffuse on the film surface and enhance the hydrophobicity of the film.

[0151] AFM images of the films are shown in Figure 2. Figure 3 As shown in Figure A, from left to right are the two-dimensional morphology, cross-sectional profile, and three-dimensional morphology of the film. Within the scanning range of 5μm×5μm, it can be seen from the two-dimensional and three-dimensional figures that with the increase in the amount of CM added, the roughness of the film also increases. It can also be seen from the cross-sectional profile that the thickness of the film also gradually increases with the increase in the amount of CM added. In addition, the average roughness (Ra) and root mean square roughness (Rq) parameters of the film surface are also analyzed. Figure 3 It can be seen from Figure B that the single CS film is relatively smooth. As the amount of CM added increases, Ra and Rq both increase gradually, and the roughness of the film increases.

[0152] The XRD pattern of the film is shown in Figure 4As shown in A, a single CS film has a broad and weak diffraction peak at 2θ=20°, indicating that its molecular arrangement is amorphous. CM reaches peaks at 10.1°, 18.3°, 30.0°, and 43.1°. Films with different CM additions also have the same diffraction peak at 2θ=20°. With the increase of CM addition, strong characteristic peaks appear at 2θ=10.1° and 18.3°, and gradually increase. With the increase of CM addition, its crystalline properties and diffraction characteristic peaks gradually appear.

[0153] The FTIR spectrum of the film is shown in Figure 4 As shown in B, the cross-linking effect caused by the interaction between CS and CM affects the position and intensity of the peak. -1 The peak at 2880cm is caused by the hydrogen bond between CS and glycerol. -1 The peak at 1636 cm is generated by the alkane group CH of CS. -1 The peak at 1550cm is caused by the hydrogen bonding of CM, which also confirms the existence of CM. -1 The peak at 1410cm is related to the bending vibration of -NH2. -1 The peak at 1150cm is generated in the CH deformation band. -1 The peak at 1030cm is due to the OH bending vibration caused by the CS structure. -1 The peak at is related to the vibration of COC. In summary, after the addition of CM, the functional groups in the CS film did not change significantly, proving that CS and CM have good compatibility.

[0154] 3. Solubility, swelling rate and water content

[0155] The solubility, swelling ratio and water content of different films are shown in Table 1. Compared with the single CS film, the addition of CM reduced the solubility, swelling ratio and water content of the film. This may be due to the hydrogen bonds formed between CS and CM, which hindered the interaction between the chitosan matrix and water, or because the hydrophobicity of CFO affected the diffusion of water molecules in the film.

[0156] Table 1 Solubility, swelling rate and water content of different films

[0157]

[0158] 4. Thickness and mechanical properties

[0159] The thickness of single CS film and composite films with different CM addition amounts are shown in Table 2. Compared with single CS film, the film thickness increases with the increase of CM addition amount. This may be due to the increase of intermolecular interactions in the film, which makes the film structure more compact and leads to the increase of film thickness. TS and EB are both indicators to measure the flexibility and strength of the film. With the addition of CM, the elongation at break and tensile strength of the film both show a trend of increasing first and then decreasing.

[0160] As can be seen from Table 2, the addition of CM significantly improves the mechanical properties of the film. When the addition amount is 5%, the elongation at break and tensile strength of the film are the highest. This may be due to the unique lamellar structure of CM, which strengthens its cross-linking effect with the chitosan matrix, thereby enhancing the mechanical properties of the film. When the addition amount is 7%, the mechanical properties of the film decrease, which may be caused by the increase in the water content in the film.

[0161] Table 2 Thickness, TS, EB and WVT of different films

[0162]

[0163]

[0164] 5. UV blocking properties

[0165] The ultraviolet light blocking property of the film is one of the important indicators to measure its quality. The experiment records the absorbance of different films under 200nm-800nm ​​ultraviolet radiation. Figure 5 As shown in Figure A, with the increase of CM addition, the film's ability to block ultraviolet light gradually increases. It can be concluded that after adding CM, the film has excellent ultraviolet light shielding performance and can effectively prevent ultraviolet light from irradiating food. In addition, the irradiation of light sources can increase the photodynamic properties of CM and improve the film's inhibitory effect on microorganisms.

[0166] 6. Water vapor transmission rate and water contact angle

[0167] Water vapor transmission rate (WVT) is an important indicator to measure the water vapor permeability of a film. In order to ensure food quality, the WVT value should be kept as low as possible. The WVT of different films is shown in Table 2. After adding CM, the WVT of the film decreased significantly, indicating that the increase in the amount of CM added can enhance the hydrophobicity of the film. Figure 5 The same results were obtained in Figure B. With the addition of CM, the water contact angle of the film increased from 87.7° to 107°, and the film changed from a hydrophilic film to a hydrophobic film. The increase in the hydrophobicity of the film may be due to the increase in the film thickness due to the addition of CM or the formation of intermolecular hydrogen bonds between CM and CS, which hindered the diffusion of water molecules.

[0168] 7. Thermal analysis

[0169] Thermal stability is an important indicator that affects the application of films in food preservation. The DSC curves of different films are as follows: Figure 5 As shown in Figure C, the DSC curves of all films have a single glass transition temperature (Tg), and the single CS film has a maximum endothermic peak at 121°C. The starting temperature, peak temperature, and end temperature change slightly with the addition of CM. The ΔH value of the film increases with the addition of CM. The results show that the components of the film have good thermal stability and compatibility.

[0170] 8. DPPH removal rate

[0171] The DPPH removal rate of different films is given by Figure 6 As shown in the figure, with the increase of CM addition, the DPPH removal rate of the film increased, with the highest level being 47% (CS / 7% CM). This may be due to the fact that CM has peroxidase and catalase mimicking activity, which can improve the antioxidant capacity of the film and help prevent the oxidative degradation of nutrients in food.

[0172] 9. Antibacterial properties

[0173] The antibacterial effects of different films on Escherichia coli, Staphylococcus aureus and Aspergillus niger after dark and light treatment are as follows Figure 7 As shown in A, B and C. With the addition of CM, the antibacterial properties of the film gradually increased. This may be due to the presence of multivalent Co and Fe ions in CM, which have good photodynamic properties and excellent mimetic enzyme catalytic activity. The ions released by CM can contact the cell wall of microorganisms, thereby destroying the surface of microorganisms, causing the contents to seep out and eventually the death of the microorganisms. The film exhibits a better inhibitory effect on Gram-positive bacteria than on Gram-negative bacteria, which can be attributed to the difference in the composition of the cell walls of the two bacteria. The cell wall of Gram-negative bacteria is composed of hydrophilic lipopolysaccharides, which can hinder the entry of hydrophobic substances. Comparison Figure 7 The medium light (6h) group and the light (0h) group showed that the inhibition effect on microorganisms was significantly improved after photocatalysis. The inhibition rates of CS / 7% CM film on Staphylococcus aureus, Escherichia coli and Aspergillus niger were as high as 99.7%, 99.8% and 97.1%, respectively. This can be attributed to the ·OH produced by CM as a photosensitizer, which induced the peroxidation reaction of intracellular substances and ultimately led to the death of microorganisms.

[0174] Table 3 Antibacterial properties of different films

[0175]

[0176] 10. Kyoho grape preservation experiment

[0177] (1) Appearance of grapes

[0178] like Fig. 9 As shown in the figure, the appearance changes of grapes stored for 12 days under different packaging conditions were recorded. For the blank group, that is, grapes without any packaging, obvious wrinkles were shown on the 12th day. This may be due to the water loss caused by long-term exposure to the air. The single CS film has a certain water barrier property, which slows down the water loss of grapes. However, a certain degree of wrinkles can still be observed. The CS / 5% CM film can still maintain its intact appearance on the 12th day, which is attributed to its strong barrier property to water molecules. Due to its limited antibacterial properties, the PE film has caused the grapes to be contaminated by microorganisms on the 12th day, and has lost the meaning of preservation.

[0179] (2) Hardness and weight loss rate

[0180] The hardness changes of grapes stored under different packaging conditions are as follows Figure 8 B. The hardness of the air group and CS film decreased faster than that of the CS / 5% CM film, which also confirmed that the CS / 5% CM film had better retention performance. Figure 8 C. The weight loss rate of grapes in the air group was the highest during storage, while after using the CS / 5% CM membrane, the weight loss rate of grapes dropped from 18.9% to 13.5%. The structure shows that the CS / 5% CM membrane can effectively prevent the penetration of water molecules and preserve the moisture of fruits.

[0181] (3) Titratable acid, soluble solids and Vc

[0182] The changes of titratable acidity in grapes during storage are as follows: Figure 8 D. The lower TA reduction rate of CS / 5% CM film may be due to the fact that the addition of CM improves the gas barrier properties of the film (reducing O2 content and increasing CO2 content), inhibiting the production of ethylene, thereby reducing the consumption of organic acids. The excellent barrier properties of CS / 5% CM film can inhibit the respiration and metabolism of fruits and reduce the loss of nutrients. Therefore, the reduction rates of soluble solids and Vc of CS / 5% CM film during storage are lower than those of other components, such as Figure 8 As shown in Figure EF, the contents were 13.5% and 4.47 mg / 100 g on the 12th day of storage. In addition, the excellent UV shielding ability of CS / 5% CM film further reduced the loss of Vc.

[0183] (4) POD activity and CAT activity

[0184] Changes of POD and CAT activities in grapes during storage Figure 8 After adding CS / 5% CM membrane, the POD and CAT activities of grapes increased by 23 and 15 U·g -1 ·min -1Increased to 29 and 19 U·g -1 ·min -1 This is attributed to the antioxidant activity of POD and CAT mimetic enzymes in CM, which can inhibit the oxidation reaction during grape storage to a certain extent, slow down fruit softening, and maintain fruit quality.

[0185] Comparative Example 1

[0186] The composite process between CM and CS was studied. The picture of single CM is shown in Fig.10 A, CM was directly mixed with CS solution, the results are shown in Fig.10 B, it can be seen that the CM cannot be well dispersed. CM was first mixed with ultrapure water, and then mixed with CS aqueous solution. Fig.10 C, indicating that the dispersion of the two is still poor. Ultrasonic mixing was performed by the method of Example 1 of the present invention, and the results are shown in FIG. Fig.10 D, indicating that the two can be well dispersed.

[0187] Comparative Example 2

[0188] As shown in the research results in Table 3, when the concentration of CM is 5%, the solubility, water content and swelling rate of the composite membrane can be kept at the lowest level, which can better ensure the film-forming performance of the composite membrane. Therefore, the CM concentration of 5% is selected for better results.

[0189] Comparative Example 3

[0190] As shown in the research results in Table 4, when the concentration of CM is too high, the performance of the composite membrane will be significantly reduced. Therefore, when the concentration of CM in the composite membrane is 5%, the effect is better.

[0191] Comparative Example 4

[0192] As shown in the research results in Table 3, when the concentration of CM is 5%, the inhibition rates of the obtained composite membrane against Staphylococcus aureus, Escherichia coli and Aspergillus niger are as high as 98.1%, 99.6% and 96.4%, respectively, and the antibacterial effect is extremely significant.

[0193] Comparative Example 5

[0194] The volume ratio of CS and CM was investigated. When the ratio of CS to CM was less than 19:1 (reducing the volume of CS while keeping the volume of CM unchanged, when 66.5 mL of CS solution and 3.5 mL of CM were mixed, the volume ratio was 19:1), CM could not be completely dissolved in the CS solution, and the film could not be prepared at this time. The dispersion of the two after mixing is shown in Figure 2. Fig.11 .

[0195] When the ratio of CS to CM is greater than 19:1 (increasing the volume of CS while keeping the volume of CM unchanged), although CM can be completely dissolved in CS, it will lead to a decrease in the performance of the film after being made. Its mechanical properties are shown in Table 4 below:

[0196] Table 4 Mechanical properties of films with different ratios

[0197]

[0198] The antibacterial properties of the composite membrane are shown in Fig.12 , it can be seen that the ratio of CS to CM greater than 19:1 will lead to a decrease in the antibacterial performance of the composite film.

[0199] The thermal stability of the composite film can be seen Fig.13 It can be seen that the ratio of CS to CM greater than 19:1 will lead to a decrease in the thermal stability of the composite membrane.

[0200] The UV absorption properties of the composite film are shown in Fig.14 , it can be seen that the ratio of CS to CM greater than 19:1 will lead to a decrease in the UV absorption performance of the composite film.

Claims

1. A method for preparing an iron-cobalt oxide / two-dimensional nitride / chitosan composite antibacterial cling film, characterized in that: The following steps are involved: (1) adding lithium fluoride to hydrochloric acid to synthesize a two-dimensional nitride with aluminum titanium carbide by an in-situ etching method; (2) synthesizing iron-cobalt oxide by a hydrothermal method using ferric chloride hexahydrate, cobalt chloride hexahydrate, sodium acetate and sodium hydroxide; (3) mixing the two-dimensional nitride and the iron-cobalt oxide in a weight ratio of 1:1, dissolving the mixture in water, and ultrasonically treating the mixture in an ice bath to obtain a nanozyme composed of the iron-cobalt oxide and the two-dimensional nitride; (4) Dissolving chitosan and glycerol in 1% by volume acetic acid solution to prepare a chitosan solution, wherein the mass percentage of chitosan is 3%; then mixing the nanozyme obtained in step (3) with the chitosan solution to obtain a composite solution, and making the volume ratio of the nanozyme 5%. Subsequently, pouring the composite solution after ultrasonic treatment into a mold, drying to obtain a film, cooling to room temperature and then removing the film, the composite antibacterial cling film is obtained.

2. The preparation method according to claim 1, characterized in that: The volume ratio of the chitosan solution to the nanozyme solution in step (4) is 19:

1.

3. The preparation method according to claim 1, characterized in that: The weight ratio of lithium fluoride to aluminum titanium carbide in step (1) is 1:1; the synthesis reaction is carried out at 35° C. for 24 hours.

4. The preparation method according to claim 1, characterized in that: The weight ratio of ferric chloride hexahydrate, cobaltous chloride hexahydrate, sodium acetate and sodium hydroxide in step (2) is 18:19:90:

25.

5. The preparation method according to claim 1, characterized in that: The conditions of the synthesis reaction in step (2) are 180° C. for 12 hours.

6. The preparation method according to claim 1, characterized in that: The hydrothermal method in step (2) is carried out in an ethylene glycol solution.

7. The preparation method according to claim 1, characterized in that: The ultrasonic time in step (3) is 0.5 hours.

8. The preparation method according to claim 1, characterized in that: The ultrasonic treatment conditions in step (4) are ultrasonic treatment at 40° C. for 4 h.

9. The iron-cobalt oxide / two-dimensional nitride / chitosan composite antibacterial fresh-keeping film prepared by the method according to any one of claims 1 to 8.

10. Use of the iron-cobalt oxide / two-dimensional nitride / chitosan composite antibacterial fresh-keeping film according to claim 9 in the preparation of antibacterial fresh-keeping materials for fruits and vegetables.

Citation Information

Patent Citations

  • Preparation method of chitosan composite preservative film

    CN106883465A

  • Copper-containing nano-enzyme composite film and preparation method thereof

    CN116948228A

  • Chitosan-polysaccharide-based composite film containing two-dimensional COFs, preparation method of chitosan-polysaccharide-based composite film and application of chitosan-polysaccharide-based composite film in olive preservation

    CN118456979A

  • Nano enzyme, antibacterial film, preparation method and application

    CN118930888A

Cited By

  • Coffee residue extract composite fresh-keeping coating liquid containing chitosan and hydroxypropyl starch, preparation method of coffee residue extract composite fresh-keeping coating liquid and application of coffee residue extract composite fresh-keeping coating liquid in storage and transportation fresh keeping of thin-skin fruits

    CN121970807A